Исследование содержания факторов роста и фактора некроза опухоли-α в биоптатах костной ткани альвеолярных отростков челюстей крыс после имплантации гидроксиапатитсодержащими материалами, фиксируемыми на различных носителях (Эндодонтия Today, 2020)
Results of research have shown that for 14th days of a reparation of a bone tissue of an alveolar shoot of the top jaw of rats under the influence of a material Osteoindutsin more active synthesis of factors of growth in comparison with a material Osteomatriks is observed.